2022
DOI: 10.1038/s41598-022-10707-w
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing ease of whelping and its relationship with maternal behaviour and puppy perinatal mortality in commercially bred dogs

Abstract: For dog breeders, parturition is a critical stage in the reproductive cycle of the dam. Evidence in other mammals suggests that a difficult labour can influence maternal behaviour and offspring viability during the first hours postpartum. However, the effect of whelping difficulty on the onset of maternal behaviour has not yet been investigated in domestic dogs. Here we developed an ease of whelping (EoW) index in dams maintained within a Commercial dog Breeding Establishment (CBE) environment and investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 94 publications
(155 reference statements)
0
4
0
Order By: Relevance
“…A previous study found that both periparturient and early maternal behaviour differed between CBE dams that were born and reared within that particular CBE and mothers brought in after 6 months of age. Dams reared outside the CBE were more restless during parturition and spent less time nursing their puppies in the first 24 h postpartum, probably reflecting higher stress levels and reactivity (Baqueiro-Espinosa et al, 2022). It is possible that some of the dams included in our study were reared in a different environment before being introduced to the CBE and were, thus, likely to be more anxious during the tests.…”
Section: Discussionmentioning
confidence: 98%
“…A previous study found that both periparturient and early maternal behaviour differed between CBE dams that were born and reared within that particular CBE and mothers brought in after 6 months of age. Dams reared outside the CBE were more restless during parturition and spent less time nursing their puppies in the first 24 h postpartum, probably reflecting higher stress levels and reactivity (Baqueiro-Espinosa et al, 2022). It is possible that some of the dams included in our study were reared in a different environment before being introduced to the CBE and were, thus, likely to be more anxious during the tests.…”
Section: Discussionmentioning
confidence: 98%
“…A similar result was obtained in the present study, where the proportion of stillbirths was higher in primiparous bitches in G 4. Apart from the higher frequency of stillbirths, primiparous bitches have an increased risk of requiring C-sections ( p = 0.004), and this is directly related to the presence of stillborn puppies ( 40 ). Some authors attribute this effect to the longer parturition duration and the lack of experience in primiparous bitches ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the quality and amount of nutrients obtained during gestation influence fetal growth ( 56 ). Another study assessing the influence of breed and average weight found that puppies of medium-sized breeds (10–20 kg) had 0.99 times lower perinatal mortality rates than large breeds (> 20 kg) ( 40 ). Regarding parity, the higher weight recorded in puppies born from multiparous dams in this study is different from the results of Tesi et al ( 57 ) in toy and small-sized dogs, as parity did not affect puppies’ birth weight or neonatal mortality in that study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation